Bocor Alus Podcast: An Analysis of the Political Role of Media Tempo During the 2024 Presidential Election - W Suhaeb, Firdaus; Amsal, Bahrul; Wahda, Muhammad Aksha (Pinisi Journal of Sociology Education Review, 2025)
This article aims to analyze how the media, particularly Tempo, plays a role in shaping the discourse of democracy during the 2024 Presidential Election in Indonesia. The main focus of this research is the analysis of the political role of the podcast program "Bocor Alus Politik" managed by Tempodotco during the 2024 presidential election, through the ideas of freedom of expression, equality, and the formation of public opinion. Through a qualitative content analysis approach that involves a deep understanding of the meaning of communication, this research explores, first, how the narratives presented by Tempodotco, particularly through the program Bocor Alus Politik, discuss, reflect, shape, and discourse political issues within the framework of media politics. Second, through the media politics framework, this article examines how the program Bocor Alus Politik plays a role in revitalizing the democratic agenda during the 2024 presidential election period. The exploration results of this article conclude, first, that through the program "Bocor Alus Politik," Tempo plays a media political role in shaping the political discourse during the 2024 presidential election period. Second, through the political narrative of "Bocor Alus Politik," Tempo has implications for the democratic process in Indonesia.